A Poet with His Philosopher's Hat On. (20th May 2021) - Livio, Chiara
Abstract : The present article is a preliminary study of a section of the seventeenth canto of Mankha's Srikanthacarita, a 'court epic' (mahakavya) in Sanskrit composed during the twelfth century in Kashmir. In the section in question (SKC 17.18-33), the author elaborates a praise of the god in the guise of a philosophical discussion introducing the views of different doctrines, with the scope of establishing the superiority of the 'non-dual' (advaita) Saivism from Kashmir. Mankha, however, does not criticize or diminish the previous traditions but borrows their concepts to enhance his own credo, making the section a successful example of inclusivism. What stands out is Siva's pervasiveness and oneness, which seems to be built upon the model of the philosophical Tantric school of the Pratyabhijna. While presenting the structure of the philosophical section, this study explores the influence of Utpaladeva (c.925-975 ce) and Abhinavagupta (c.975-1025 ce) on Mankha's ideology.